No Man's Land : Tussen kunst en design - Verbeke Foundation, Kemzeke (Kemzeke : Verbeke Foundation Kemzeke, 2007)
Angeloni, Franco ; Bakker, Thijs ; De Beer, Geoffrey ; uit den Bogaard, Martin ; Bervoets, Fred ; Van Braak, Kevin ; Broich, Christoph ; Van Breedam, Camiel ; Buggenhout, Peter ; Carlier, Maurice ; Coolen, Caroline ; Claessens, Roger ; Castelyns, Frank F. ; De Cordier, Louis ; De Cupere, Peter ; van Dijck, Bart ; Deguislage, Delphine ; Ebinger, Moritz ; Fabre, Jan ; van Hemelrijck, Kris ; Van Hove, Eric ; Happy Famous Artists ; Grard, Chantal ; van Gogh, Dirk ; Idiots ; Kuyl, Chiel ; ILAP ; Kuster, Jeroen ; Korstanje, Maartje ; Lagendijk, Reinier ; Lust, Xavier ; Wynants, Dirk ; Linnares, Michael ; Likely, Seymour ; van Lieshout, Joep ; Meijman, Sjef ; Muller, Sofie ; Oskamp, Jurgen ; Van Nazareth, Herman ; Nachtwacht Research Project ; Otten, Dries ; Van Praet, Frans ; De Pelsmacker, Hans ; Pillen, Sarah ; Quinze, Arne ; van Riet, Peter ; Segers, Paul ; Schuurmans, Rolf ; Vanseveren, Hannes ; Szukalski, Albert ; Ulrichs, Timm ; Vanmechelen, Koen ; Volckaert, Tim ; Veranneman, Emiel ; Verschuren, Geert ; de Wilde, Frederik ; De Winter, Ronald ; Wenners, Julia ; De Zutter, Bart
Nederlands
Exhibition. No Man's Land : Tussen kunst en design. Verbeke Foundation Kemzeke. 2007-12-15. 2008-05-04
boek